Microarray Gene Expression Data Analysis - Liew, Alan Wee‐Chung; Gan, Xiangchao (Algorithms in Computational Molecular Biology: Techniques, Approaches and Applications, 2011)
This chapter contains sections titled: Introduction DNA Microarray Technology and Experiment Image Analysis and Expression Data Extraction Data Processing Missing Value Imputation Temporal Gene Expression Profile Analysis Cyclic Gene Expression Profiles Detection Summary Acknowledgments References